Long-term effects of group exercise intervention on maximal step-up height in middle-aged female primary care patients with obesity and other cardio-metabolic risk factors - Lillemor A. Nyberg; Carl Johan Sundberg; Per Wändell; Jan Kowalski; Mai-Lis Hellénius (BMC, 2020)
Abstract Background Low physical performance is a predictor of morbidity and mortality. This study looks at long-term effects of an exercise intervention on maximal step-up height (MSH) in individuals with low physical function. Factors associated with changes in MSH was studied. Methods Female patients (n = 101), mean (SD) age of 52 (11) years, were recruited for a 3-month group exercise intervention including 2-3 sessions/week of mixed aerobic fitness and strength training. MSH, weight, body mass index (BMI), waist circumference, maximal oxygen consumption (VO2-max), self-reported health (SF-36) and physical activity (PA) were measured at baseline (T0), after 3 months (T1) and after 14-30 (mean 22) months (T2). Relationships between changes in MSH (cm) and age, baseline MSH, time to follow-up, changes in anthropometric measurements, VO2-max, SF-36 and PA were studied with regression analyses. Results MSH, significantly, increased from T0 to T1, 27.2 (5.7) to 29.0 (5.5) cm and decreased to 25.2 (5.5) cm at T2. Time to follow-up (B = − 0.42, p < 0.001) and change in BMI (B = − 0.29, p = 0.012) correlated significantly to changes in MSH. Waist circumference, VO2-max, PF and exercise/physical activity levels were significantly improved at T2, while BMI did not change. In a univariate logistic regression model, maintenance of MSH correlated to the extent of mixed training (OR 3.33, 95% CI 1.25-8.89). In a multivariate logistic regression model adjusted for important factors the correlation was not significant. However, MSH was significantly higher in individuals participating in 2-3 session per week compared to one session. Conclusions A 3-month group exercise intervention increased MSH, improved fitness, decreased risk in female patients with elevated cardio-metabolic risk. After an average of 22 months MSH was reduced while positive effects remained for waist circumference, VO2-max, physical function and physical activity. However, regular group exercise 2-3 times per week with mixed aerobic fitness and strength training was associated with maintenance of MSH in a subgroup of patients. We suggest that such an intervention including regular support from healthcare professionals is a successful approach for maintaining improved leg-muscle strength among primary care patients. Trial registration ISRCTN21220201 September 18, 2019, retrospectively registered.